2015
DOI: 10.1016/j.drugpo.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Are risk factors for drug use and offending similar during the teenage years?

Abstract: Results show that the factors included here are more appropriate to understanding offending than drug use. Different risk factors are associated with drug use and offending in the older, but not younger teens. It is argued that later in the teenage years drug use should be understood and addressed differently to offending. This is particularly important given the tendency for the 'drugs problem' to increasingly be dealt with as a 'crime problem' (Duke, 2006).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In our study, moderate to high level of ND and weekly use of stimulants in adolescence were prominent predictors for drug crime offending. There are several studies showing that smoking tobacco in adolescence can increase the likelihood for criminal offending (Aston 2015) and that, in adulthood, smoking tobacco increases the possibility of drug crime offending (Elonheimo et al 2011). Jurmu et al (2020) reported that higher levels of ND in adolescence predicted greater levels of drug crime offences committed up to young adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, moderate to high level of ND and weekly use of stimulants in adolescence were prominent predictors for drug crime offending. There are several studies showing that smoking tobacco in adolescence can increase the likelihood for criminal offending (Aston 2015) and that, in adulthood, smoking tobacco increases the possibility of drug crime offending (Elonheimo et al 2011). Jurmu et al (2020) reported that higher levels of ND in adolescence predicted greater levels of drug crime offences committed up to young adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Young people with a history of physical or sexual abuse are also at higher risk of developing problems with both criminality and drugs (Brunelle et al 2014; Nooner et al 2012). Involvement with peers who have been convicted of offences and often use illegal drugs is one of the most significant factors for both problems (Aston, 2015; Hoeben, Meldrum, Walker, & Young, 2016). Non-participation in structured recreational activities with prosocial peers seem to increase the risk of later drug use (Stone et al 2012).…”
Section: Introductionmentioning
confidence: 99%